Gambaran Kesiapsiagaan Masyarakat Terhadap Penanggulangan Bencana Banjir Di Wilayah Kelurahan Nyunyai Kecamatan Rajabasa Kota Bandar Lampung: Community, Preparedness, Flood Disaster - Ningrum, Dyah Intan Kusuma; Romayati, Umi; Novikasari, Linawati; Winarno, Rudi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: According to the Lampung Regional Disaster Management Agency (BPBD), there were 10 recorded flood incidents across Bandar Lampung, South Lampung, Pesawaran, and Tulang Bawang throughout February 2024. Among these events, flooding was the most prevalent, resulting in damage to 235 buildings and financial losses estimated at approximately 155 million rupiah. Objective: This study aims to provide an overview of community preparedness in flood disaster management in the Nyunyai Sub-district, Rajabasa District, Bandar Lampung City. Method: This research employed a descriptive study design using a cross-sectional approach. The study was conducted in Neighbourhood I (LK I) of Nyunyai Sub-district, which includes four neighbourhood units (RT). The total population consisted of 283 households, with a sample of 166 households selected using probability sampling through proportionate stratified random sampling. Data were analysed using univariate analysis. Results The findings show that the vast majority of respondents demonstrated a “prepared” level of flood readiness, with 150 individuals (90.4%) falling into this category, and 6 individuals (3.6%) categorized as “very prepared.” However, 10 individuals (6.0%) were found to be “less prepared.” Conclusion: The study concludes that the majority of respondents in LK I, which includes RT 3, RT 5, RT 6, and RT 8 of Nyunyai Sub-district, are in the “prepared” category (90.4%) in terms of flood disaster preparedness. It is recommended that residents actively participate in disaster preparedness activities such as simulations, training, and public education sessions. In addition, households are encouraged to prepare emergency equipment and develop family evacuation plans in anticipation of future flood events.